Ownership, Capital or Outsourcing: What Drives German Investment to Eastern Europe? - Dalia Marin; Andzelika Lorentowicz; Alexander Raubold (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2002)
The paper takes a first look at the host and home country effects of German FDI in Eastern Europe (EE) based on new survey data of 1050 investment projects in EE by 420 German multinationals during the 1990s. We find that German investors transfer a substantial amount of financial capital to EE. Furthermore, the most dynamic and innovative segment of the German economy invests in the East which explains why single owned firms dominate as the form of control. We also find strong evidence of vertical FDI suggesting that German cororations are outsourcing a substantial share of their production to EE affiliates to exploit lower wages in the East.
urn:nbn:de:bvb:19-epub-72-5
Keywords: F15; F21; G32; G34; 330; capital flows; vertical vs. horizontal FDI; corporate governance; globalization; Eastern Enlargement